ArchBukhta. Refraction/23 - Malinovich, Roman; Chichkan, Alexandra (project baikal, 2023)
From 7 to 12 March, the 17th All-Russian Architectural Festival “ArchBukhta. Refraction” was held at the forum site of the AllRussian Youth Environmental Campus ECO.TSEKH on the territory of the former BPPM. The theme is interpreted broadly – from physical phenomena to human experiences. The article describes the works of the Festival winners.